2018
DOI: 10.24251/hicss.2018.573
|View full text |Cite
|
Sign up to set email alerts
|

Role of CDOs in the Digital Transformation of SMEs and LSEs - An Empirical Analysis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 26 publications
2
17
0
6
Order By: Relevance
“…However, the entire company would also be digitalized by ''transforming the existing business model into the digital world, developing new business models to drive the business forward into the future'' (SME 19). In line with Hess et al (2016) and Becker et al (2018), the study shows that both SMEs and LSEs understood the fundamental idea of the digital transformation and the need for a suitable digital strategy. The basic purpose is to use all the advantages of digital transformation to survive in the digital age.…”
Section: Purpose Of the Digital Strategy In Smes And Lsessupporting
confidence: 62%
See 3 more Smart Citations
“…However, the entire company would also be digitalized by ''transforming the existing business model into the digital world, developing new business models to drive the business forward into the future'' (SME 19). In line with Hess et al (2016) and Becker et al (2018), the study shows that both SMEs and LSEs understood the fundamental idea of the digital transformation and the need for a suitable digital strategy. The basic purpose is to use all the advantages of digital transformation to survive in the digital age.…”
Section: Purpose Of the Digital Strategy In Smes And Lsessupporting
confidence: 62%
“…In particular, it is crucial whether companies make use of technology that already exists on the market or whether they act as market leaders through their own creation of new technology. Horlacher and Hess (2016) and Becker et al (2018) come to the same conclusion in their studies because they found that companies of all sizes-including both SMEs and LSEs-have to understand the role of new digital technologies, as these can disruptively change the existing business model. In addition, these new digital technologies result in new opportunities, but also threats for all company sizes (Haffke et al 2016;Leischnig et al 2016).…”
Section: Theoretical Frameworkmentioning
confidence: 84%
See 2 more Smart Citations
“…Implementing the role of the CDO is also seen as one of the main challenges for SMEs (Becker, Schmid & Botzkowski, 2018). Its roles differ significantly from those of CDOs in larger companies: In SMEs, the CDO's primary responsibility lies in digitization and strategic management.…”
Section: The Situation In Small and Medium Enterprisesmentioning
confidence: 99%